Application and analysis of a model based controller for cooling towers in compression chiller plants. Issue 2 (February 2020) - Sawant, Parantapa; Ho, Eric; Pfafferott, Jens
Abstract: Cooling towers or recoolers are one of the major consumers of electricity in a HVAC plant. The implementation and analysis of advanced control methods in a practical application and its comparison with conventional controllers is necessary to establish a framework for their feasibility especially in the field of decentralised energy systems. A standard industrial controller, a PID and a model based controller were developed and tested in an experimental set-up using market-ready components. The characteristics of these controllers such as settling time, control difference, and frequency of control actions are compared based on the monitoring data. Modern controllers demonstrated clear advantages in terms of energy savings and higher accuracy and a model based controller was easier to set-up than a PID. Abstract : Systems engineering; Energy; Control system design; Energy conservation; Energy use in building; Mechanical systems; Process modeling; Cooling tower process control; Control engineering applications; Experimental analysis; Model based control